2015
DOI: 10.1155/2015/747830
|View full text |Cite
|
Sign up to set email alerts
|

Litsea japonicaExtract Inhibits Aldose Reductase Activity and Hyperglycemia-Induced Lenticular Sorbitol Accumulation in db/db Mice

Abstract: Aldose reductase (AR) is the first and rate-limiting enzyme of the polyol pathway. AR-dependent synthesis of excess polyols leads to lens opacification in diabetic cataract. The purpose of this study is to investigate the protective effect of Litsea japonica extract (LJE) on diabetes-induced lens opacification and its protective mechanism in db/db mice. Seven-week-old male db/db mice were treated with LJE (100 and 250 mg/kg body weight) once a day orally for 12 weeks. LJE dose dependently inhibited rat lens al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Recently, it was reported that a crude extract from the leaves of L. japonica induced apoptosis of HL-60 leukemia cells [15] and significantly inhibited complement activity in vitro [16]. In our ongoing efforts to identify effective, naturally sourced therapeutic agents for diabetic complications, we found that an extract from L. japonica reduced the development of diabetic nephropathy via the inhibition of AGEs formation in db/db mice [17] and prevented diabetes-induced lens opacification via the inhibition of AR activity [18]. However, the active compounds underlying these effects of L. japonica remain unknown.…”
Section: Introductionmentioning
confidence: 91%
“…Recently, it was reported that a crude extract from the leaves of L. japonica induced apoptosis of HL-60 leukemia cells [15] and significantly inhibited complement activity in vitro [16]. In our ongoing efforts to identify effective, naturally sourced therapeutic agents for diabetic complications, we found that an extract from L. japonica reduced the development of diabetic nephropathy via the inhibition of AGEs formation in db/db mice [17] and prevented diabetes-induced lens opacification via the inhibition of AR activity [18]. However, the active compounds underlying these effects of L. japonica remain unknown.…”
Section: Introductionmentioning
confidence: 91%
“…For instance, accumulation of sorbitol produced as a result of enzymatic reduction of glucose by aldose reductase, has been established as an initiating factor for diabetic cataract pathogenesis ( 7 , 8 ). Specifically, the intracellular deposition of the polyol sorbitol causes significant osmotic changes in lens tissues, resulting in lens fiber degeneration and liquefaction, eventually inducing sugar cataract formation, lens swelling and opacities ( 4 , 9 ). In addition, the apoptosis of lens epithelial cells (LECs) is also enhanced by the osmotic stress induced by abnormal sorbitol accumulation in the lens, which is also involved in diabetic cataract formation ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The lens homogenate from each of the five groups (groups I to V) was prepared in PBS (pH 7.4). Sorbitol levels in the lens were measured as previously described [ 52 , 53 ]. Briefly, a total of 1 mL of extract from each lens was mixed with 2 mL glycine buffer (0.05 M, pH 9.4) containing 2 mM NAD (Nicotinamide adenine dinucleotide) and 0.05 mL sorbitol dehydrogenase (25.6 U/mL) and incubated at room temperature for 60 min.…”
Section: Methodsmentioning
confidence: 99%